Analisis Relasi Makna Dalam Bahasa Mandailing - Parulian Sibuea; Fatiyah Ayumi; Siti Az-zahra³, Salsabilah Nur; Rahma Fitria (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
Language has an important role in human life. Because language acts as a means of communication and has a big role in the establishment of an interaction. Indonesia has one language that is a unifying language, namely Indonesian. Meaning relations can be in the form of opposite meaning (antonym), multiplicity of meaning (polysemy), similarity of meaning (synonym), and abnormality of meaning (homonym). This research was conducted using a qualitative method that is descriptive in nature. Qualitative research is describing, explaining, and elaborating data based on the focus of the problem descriptively.. The concepts of meaning relations discussed include antonyms (opposite meanings), synonyms (similarity of meaning), and polysemy (one word with more than one meaning). Mandailing language has meaning relations that greatly affect the use of each word in certain conditions in society. The results showed that in the greeting system, there are meaning relations in the form of antonyms, synonyms, and polysemy in both Indonesian and Mandailing.